DEVELOPMENT OF SCIENTIFIC VIEWS ON THE MANAGEMENT OF AN ENTERPRISE’S EQUITY CAPITAL (INNOVATIVE ECONOMY, 2025)
Trynchuk V.V., Zelenytsa I.M., Boyko O.V.  DEVELOPMENT OF SCIENTIFIC VIEWS ON THE MANAGEMENT OF AN ENTERPRISE’S EQUITY CAPITALPurpose. The aim of the article is to provide a comprehensive analysis of the evolution of scientific approaches to enterprise equity capital management, from classical economic concepts to modern corporate finance theories, and to identify key trends and practical guidelines for financial management in a market economy.Methodology of research. General scientific and special research methods were used in the process of research, including the historical and logical method to examine the development of theoretical approaches; analysis and synthesis to generalize the provisions of classical and modern financial theories; the comparative method to compare alternative capital structure concepts; and a systemic approach to determine the role of equity capital within the enterprise financial management system.Findings. The article systematizes scientific views on enterprise equity capital management and reveals the content and significance of major capital structure theories, including the Modigliani–Miller theorem, trade-off theory, pecking order theory, agency theory, and market timing theory. The results demonstrate that there is no universal optimal capital structure, as the proportion of equity and debt capital is shaped by tax, informational, agency, and behavioural factors.Originality. The systematization of theoretical approaches to enterprise equity management has been improved by integrating classical economic concepts and modern corporate finance theories into a coherent logical model that allows for comprehensive consideration of tax, information, agency, and behavioural factors in capital structure formation. The theoretical justification for the absence of a universal optimal capital structure has been further developed by specifying the impact of the institutional environment, macroeconomic instability, and the peculiarities of enterprise functioning in Ukraine's transitional economy. Practical value. The findings can be applied in the practice of enterprise financial management when developing equity capital management policies, dividend strategies, and target capital structure benchmarks aimed at enhancing financial stability and business value.Key words: equity capital, capital structure, financial management, trade-off theory, pecking order theory, agency costs, market timing.
Keywords: equity capital; capital structure; financial management; trade-off theory; pecking order theory; agency costs; market timing